2022
DOI: 10.3390/ijerph19052645
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Teachers’ Psychological Distress and Work Engagement during COVID-19 Outbreak: The Protective Role of Mindfulness and Emotion Regulation

Abstract: COVID-19 has dramatically affected the mental health and work environment of the educational sector. Our primary aim was to investigate preschool teachers’ psychological distress and work engagement during the COVID-19 outbreak, while examining the possible protective role of participating in a mindfulness-based intervention geared to foster compassion (Call2Care-Israel for Teachers; C2C-IT) and emotion regulation. The prevalence of emotional distress, work engagement, and COVID-19 concerns were evaluated in 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 65 publications
(85 reference statements)
0
9
1
Order By: Relevance
“…This finding is in accord with Deng et al who found that self-monitoring as an attribution of higher-order thinking skills leads to individuals' engagement and self-efficacy. In the same vein, Keleynikov et al (2022) highlighted that teachers' mindfulness and thinking strategies were the key factors in their enjoyment and management of psychological distress. As the results display, the more EFL learners lie on cognitive and metacognitive strategies of thinking skills the better they can perform inclass activities and assessments (model 2).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accord with Deng et al who found that self-monitoring as an attribution of higher-order thinking skills leads to individuals' engagement and self-efficacy. In the same vein, Keleynikov et al (2022) highlighted that teachers' mindfulness and thinking strategies were the key factors in their enjoyment and management of psychological distress. As the results display, the more EFL learners lie on cognitive and metacognitive strategies of thinking skills the better they can perform inclass activities and assessments (model 2).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study revealed that effective emotion regulation was associated with improved management of teachers’ anger—an important finding in the context of emotional dynamics within the teaching profession. Turning our attention to another study by Keleynikov et al (2022) , they ventured into the realm of preschool teachers to explore the potential impact of a mindfulness-based intervention aimed at nurturing compassion and emotion regulation. The outcomes were indeed remarkable, as teachers who participated in the intervention reported lower levels of emotional distress, while simultaneously exhibiting higher utilization of adaptive emotion regulation strategies, culminating in elevated levels of work engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the beginning of the COVID-19 pandemic, the well-being of teachers has been detrimentally affected (Keleynikov et al, 2022). In fact, a study conducted in Canada showed that over 1,000 teachers reported increased stress related to their profession directly related to the novel circumstances of the pandemic (Sokal et al, 2020).…”
Section: Leading Staff and Students Through Crisismentioning
confidence: 99%